Evaluating Streptococcus mutans Strain Dependent Characteristics in a Polymicrobial Biofilm Community - Zhou, Yan; Millhouse, Emma; Shaw, Tracy; Lappin, David F.; Rajendran, Ranjith; Bagg, Jeremy; Lin, Huancai; Ramage, Gordon (Frontiers in Microbiology, 2018)
Purpose: The purpose of this study was to investigate strain dependent differences of the cariogenic biofilm forming Streptococcus mutans within both simple and complex communities. Methods: A mono-species containing representative Streptococcus mutans clinical isolates (caries and non-caries), and a multispecies in vitro caries biofilm model containing Lactobacillus casei, Veillonella dispar, Fusobacterium nucleatum and Actinomyces naeslundii, and either of two representative Streptococcus mutans clinical isolates (caries and non-caries), was developed as a comparison model. Compositional analysis of total and live bacteria within biofilms, and transcriptional analysis of biofilm associated virulence factors were evaluated by live/dead PCR and quantitative PCR, respectively. Scanning electron microscopy (SEM) was used to analyze the architecture of biofilm. One-way analysis of variance and t tests were used to investigate significant differences between independent groups of data. Results: Within a mono-species biofilm, different S. mutans strains responded similarly to one another during biofilm formation in different carbohydrate sources, with sucrose showing the highest levels of biofilm biomass and galactose showing the lowest. Within the polymicrobial biofilm system, compositional analysis of the bacteria within the biofilm showed that S. mutans derived from a caries-free patient was preferentially composed of both total and viable L. casei, whereas S. mutans derived from a caries patient was dominated by both total and viable S. mutans (p<0.001). Normalised gene expression analysis of srtA, gtfB, ftf, spaP, gbpB and luxS, showed a general upregulation within the S. mutans dominant biofilm. Conclusions: We were able to demonstrate that individual strains derived from different patients exhibited altered biofilm characteristics, which were not obvious within a simple mono-species biofilm model. Influencing the environmental conditions changed the composition and functionality S. mutans within the polymicrobial biofilm. The biofilm model described herein provides a novel and reproducible method of assessing the impact on the biofilm microbiome upon different environmental influences.